Armenia : Public Financial Management Reform Priorities - World Bank (World Bank, 2012)
The objective of this paper is to provide practical recommendations for improving the effectiveness of the public financial management system as inputs to the envisaged Armenian public financial management (PFM) reform strategy. The paper aims at providing a comprehensive analysis of most of the key elements of the financial management system thus supplementing existing analyses undertaken for each function in isolation. By doing so, the paper aims at contributing to the reaching of consensus among key stakeholders to public financial management and the financial management reform process in Armenia including within the Ministry of Finance, line ministries, elected officials, control agencies, the interested public and international partners. The report is structured as follows: chapter two provides a review of budget formulation processes. Chapter three assesses budget execution. Chapter four looks at capacity, organization and motivation and Information and Communication Technology (ICT) support issues. Finally, chapter five looks at reform scenarios, management and funding.